Experimental Studies of Thermal Hydraulics of Deep Eutectic Solvent Based on Choline Chloride - Myung Hyun Pyo; Siwon Seo; Jaeyoung Lee (International Journal of Chemical Engineering, 2022)
Molten salt reactor (MSR) is considered a promising 4th generation nuclear power plant because of its safety and suitability for SMR (small modular reactor). Also, molten salts are used in concentrating solar power (CSP) and energy storage system (ESS) as a heat storage medium. So molten salt has recently been researched a lot as heat storage and a transfer medium. However, molten salts’ high operating temperature (>450°C) and high Prandtl number make it hard to perform a thermal-hydraulic experiment in the laboratory. Thus, high Prandtl number and high viscosity fluid, deep eutectic solvents (DES), is chosen as a simulant of molten salts in this study. Thermal-hydraulic experiment using glyceline, which is easy to synthesize and transparent to visualize flow with high viscosity among various DESs, was performed. Also, the friction factor and heat transfer coefficient required for energy system designs were measured. As a result, it was found that glyceline is a Newtonian fluid, and the transition region from laminar to turbulent flow has a lower Reynolds number than water has. In addition, the heat transfer coefficient properties of glyceline were somewhat consistent with the existing correlations. To summarize, glyceline’s friction factor and heat transfer coefficient are predictable in existing theories, but the transition regions for those are different because flow development behavior between hydraulic and thermal boundary layers is different. Therefore, it is estimated that thermal-hydraulic experiments are essential when using high Pr numbers and high viscosity fluids such as DESs and molten salts as heat storage and transfer mediums.